Exploring Mature Students’ Perspectives on Task-Based Language Teaching in a Ghanaian Private University: A Qualitative Study - Susana Adjei-Mensah (Pan-African Journal of Education and Social Sciences)
Task-based Language Teaching (TBLT), a student-centered language teaching method, has emerged as an effective language teaching approach for improving the language competency levels of all students, including mature students. This study explored the perspectives of mature students who had undergone 12 weeks of TBLT at a private university. The objective was to examine the impact they had observed on their language proficiency resulting from the approach. This study was conducted to address the need for effective language instruction tailored to mature students in Ghana, where research addressing effective teaching methodologies for such groups is limited.  Using a phenomenological research design, 15 participants were interviewed in-depth for the study, with five thematic areas emerging. All the students shared their language improvement experiences. Time constraints and non-participation by some students were setbacks to this approach. However, their overall impression was positive, especially regarding their lecturers and interactions during the preparatory phase. Based on the findings, it is recommended that language teachers explore the use of TBLT to improve students' language proficiency, especially the mature ones.